ANALYSIS OF SAINTIFICATION AND SPIRITUALIZATION POLICY TRANS-INTEGRATION OF SCIENCE IN PRACTICE (CASE STUDY ON THE MULTI-FACE REALITY OF THE DEVELOPMENT OF A NEW PARADIGM OF SCIENTIFIC TRANS-INTEGRATION AT UIN SULTHAN THAHA SAIFUDDIN JAMBI) - Ismail, Ismail; Arifudin, Iis; Adimarta, Teguh; Fadlilah, Fadlilah (Dinasti Publisher, 2022)
Currently, the Science Integration paradigm that is promoted by UIN in Indonesia is still trapped in discourse, trapped in endless conceptual polemics. However, UIN Sulthan Thaha Saifuddin Jambi has a very heavy responsibility and scientific work, namely breaking down the walls of the dichotomy of science (religion and general, world and the hereafter) which has been so strong. Some of the analyzes above, regarding the advantages, disadvantages, challenges and threats of this paradigm of trans-integration of science at UIN Sulthan Thaha Saifuddin Jambi in general show: (1) Institutionally, it cannot be denied that UIN Sulthan Thaha Saifuddin Jambi has a steady status and existence as an Islamic higher education institution in Indonesia. UIN Sulthan Thaha Saifuddin Jambi skyrocketed very significantly from rank 425 to 114. (2) The first glaring weakness is the existence of an instant culture among the academic community of UIN Sulthan Thaha Saifuddin Jambi. This instant culture leads to an impatient way of thinking, eager to see the desired success immediately. (3) In addition to strengths and weaknesses, it should also be noted that there are several opportunities that can be exploited by the paradigm of trans-integration of knowledge at UIN Sulthan Thaha Saifuddin Jambi, namely the very clear opportunity that can be called the need for contemporary Islamic education for theories and concepts that linking the religious sciences and general sciences, religious sciences and the social sciences of the humanities. (4) UIN Sulthan Thaha Saifuddin Jambi which applies the paradigm of trans-integration of knowledge must also pay attention to mis-understandings and suspicions about Islam, because UIN is a campus that develops Islamic identity. It is undeniable that at this time many parties, especially in the West, view Islam as a terrorist, fundamentalist, or radical group that endangers human civilization. (5) Trans-integration of knowledge at UIN Sulthan Thaha Saifunddin Jambi itself contributes a valuable mindset for the development of contemporary science, namely the awareness not to be exclusive, not to be confined to certain scientific disciplines.